Standardisasi Ekstrak Buah Ceremai (Phyllanthus Acidus L. Skeels) dan Aktivitas Inhibisi Enzim Elastase - Ernawati, Eneng Elda; Suryani, Nani; Nuramalia, Sifa; Anisah, Anisah; Yustika, Rd. Widya (Jurnal Kartika Kimia, 2023)
One way to ensure that efficacy and quality are guaranteed is that a product/medicinal ingredient quality standard needs to be met by standardizing the extract. Ceremai fruit (Phyllantus acidus) is thought to have elastase enzyme inhibitor activity because it contains vitamin C and flavonoids. The elastase enzyme functions in skin elasticity. This research aims to determine the standardization of ceremai fruit extract (P. acidus) and the inhibitory activity of the elastase enzyme. The sample was extracted using the maceration method using 70% solvent. Parameters in determining extract standardization are specific and non-specific. The inhibitory activity of the elastase enzyme was analyzed using the ELISA method. The results of determining the standardization of extract-specific parameters, the water-soluble essence content was 65.57%, and the ethanol-soluble essence content was 27.875. Non-specific parameters for determining water content 9.17%, determining total ash content 5.68%, determining acid insoluble ash content 1.5%, determining residual solvent 0.01%, determining microbial contamination ALT and AKK 10-1, heavy metal examination with undetectable results. Ceremai fruit extract (EBC) is positive for containing flavonoids, tannins, saponins, alkaloids, steroids, and phenolic compounds. The elastase enzyme inhibitory activity of ceremai fruit extract (EBC) resulted in an average IC50 value of 281.09 ± 11,3µg/mL and retinol with an average IC50 value of 23.81 ± 0,4 µg/mL. This research concludes that based on standardization testing of specific and non-specific parameters, ceremai fruit extract meets raw material quality standards and ceremai fruit extract (EBC) has weak category elastase enzyme inhibitory activity.